Numerical and experimental analysis of the effect of volumetric energy absorption in powder layer on thermal-fluidic transport in selective laser melting of Ti6Al4V - Mishra, Ashish Kumar; Kumar, Arvind (Optics and laser technology, 2019)
[Display omitted] •Volumetric heat source has been used in modeling of SLM of Ti6Al4V.•Simulation of moving single scan and multi-scan.•Porosity is estimated and compared with the experiment.•Porosity forms due to improper melting in the powder bed.•The solidification parameters are calculated to estimate solidified grain structure. A volumetric heat source is used in numerical modeling of selective laser melting (SLM) of Ti6Al4V powder. Single track and multi-track SLM simulations are performed by varying the two key process parameters-laser power and scan speed. The model is validated with the published experimental results for melt pool shape, size and temperature. The predictions are in good agreement with the experiments at low to medium energy density. The validated model is used for investigating the thermo-fluidic transport during SLM of Ti6Al4V and examining the dependence of the melt pool characteristics on the process parameters. As-solidified porosity is calculated numerically for the multi-track simulations and its formation is delineated with the transport phenomena. The predicted porosity compares reasonably well with the experimental values. Solidification parameters, such as temperature gradients and cooling rate are calculated at the instantaneous location of the solidification front and analyzed. This analysis suggests the formation of fully columnar grains of different sizes along the width and depth of the melt pool. Overall, the model provides a good description of thermo-fluidic transport in SLM of Ti6Al4V powder and the resulting temperature field, melt pool characteristics, as-solidified porosity and the expected grain structure. Based on the current analysis, an optimum processing window of 50–70 J mm−3 energy density is suggested for SLM of Ti6Al4V powder.